DETERMINATION OF THEOBROMINE LEVELS IN CHOCOLATE BEVERAGE POWDER BY HPLC METHOD - Aprilia M.Sc. Kusbandari; Wida Safitri (Jurnal Farmasi Klinik dan Sains, 2022)
Chocolate drinks are one of the processed chocolate products that are popular among the people. Chocolate has a variety of active compounds including protein, fat, carbohydrates, polyphenol compounds, flavonoids and methylxanthine. Theobromine or 3,7-dimethylxanthine is the main ingredient in chocolate which belongs to the methylxanthine alkaloid group. This theobromine has a pharmacological effect as a stimulant. The purpose of this study was to determine theobromine levels contained in chocolate drink powder using the HPLC method. The sample used is chocolate drink beverage in the Umbulharjo Sub-District of Yogyakarta. Qualitative tests were carried out by the Parry test, the Murexide test, and comparing the retention times of samples to theobromine standards. Quantitative analysis was carried out using HPLC instruments with the mobile phase of methanol : water (40:60 v/v) with flow rate of 0.8 mL/minute, running time of 10 minutes, at λ 275 nm and stationary phase C18. Theobromine qualitative test showed that the sample contained theobromine with the Parry test is green solution, and in the Murexide test is violet red as well as the produced a relatively similar retention time of 5,789 minutes for the standard and 5,872 minutes for the sample. The average theobromine level of the three samples per dose for one cup of chocolate beverage was (18,0433 ± 0,8298) mg, (21,1753 ± 0,8716) mg, dan (32,1292 ± 1,4765) mg. Theobromine content of each sample was analyzed by Kruskal Wallis with a confidence level of 95% and the results showed a significant difference with a significance value of 0.002 <0.005. From the results of the study concluded that the sample contains theobromine which is a distinctive compound which is contained in chocolate.